PRASANGKA SOSIAL DALAM PERSPEKTIF KOMUNIKASI ANTAR BUDAYA DAN AGAMA - Mutia Tisa (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
The interaction among the individuals and groups who have different culture, different form of the communication whether verbal or nonverbal communication can cause misunderstanding in communication among the culture. So, some opinions and views toward a culture or community become the identity that traps us in creating some social prejudices. Because of that, it prevents communication and could have brought more severe consequences and can bring up offenses. In every religion, this prejudice is forbidden, especially Islam, because almost all prejudice is falsehood which can create enmity among other and this is considered as a great sin.